Fenomena Dominasi Perempuan Dalam Drama Korea Queen Of Tears - Jamiati KN (Journal on Education, 2024)
Korean dramas (K-Drama) have become a significant popular culture phenomenon in representing gender issues and the role of women. This research examines the phenomenon of female dominance in the Korean drama "Queen of Tears" which features female main characters as strong figures in the fields of business and politics. The aim of this research is to explore and understand the phenomenon of female domination represented in the drama from the audience's perspective using Alfred Schutz's phenomenological study approach. The research uses qualitative methods with a constructivism paradigm. Data collection was carried out through in-depth interviews, observation and documentation from primary data sources in the form of drama audience informants and secondary data sources in the form of related literature. The research results show that the drama "Queen of Tears" provides a complex representation of the role of women in modern society, where the main female character is depicted as a strong and ambitious leader in the business world, but also faces challenges in balancing her career and personal life. This research contributes to the understanding of the role of popular media in shaping perceptions and discourse about gender in contemporary society.